Alain Badiou Between Theology and Anti-Theology. - Phelps, Hollis (London ; New York : Routledge, 2014)
''Alain Badiou: Between Theology and Anti-theology'' provides one of the first comprehensive analyses of the relationship between Badiou''s philosophy and theology. Examining the full range of Badiou''s writings, this provocative study explores how Badiou''s philosophy relies on theology even if he claims otherwise and actively attempts to work against theology. Despite the complex questions discussed - ranging across ontology, the theory of truth and the subject, philosophy and its conditions, and anti-philosophy - this book presents a clear and accessible overview of the theological, rel.
Cover; Half Title; Title Page; Copyright Page; Table of Contents; Acknowledgements; Abbreviations; Introduction; 1. Badiou''s anti-theology; 2. Event, truth and the subject; 3. Philosophy and its conditions; 4. Badiou''s theology; Notes; Bibliography; Index
Description based upon print version of record.
Includes bibliographical references and index.
Keywords: Badiou, Alain; Philosophy and religion; PHILOSOPHY / History & Surveys / Modern; Electronic books